2021
DOI: 10.3390/s21010274
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Traffic Signal Control: Game-Theoretic Decentralized vs. Centralized Perimeter Control

Abstract: This paper compares the operation of a decentralized Nash bargaining traffic signal controller (DNB) to the operation of state-of-the-art adaptive and gating traffic signal control. Perimeter control (gating), based on the network fundamental diagram (NFD), was applied on the borders of a protected urban network (PN) to prevent and/or disperse traffic congestion. The operation of gating control and local adaptive controllers was compared to the operation of the developed DNB traffic signal controller. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Additionally, they also extended their work to the network level [18]. Furthermore, Elouni et al [19] compared the operation of game theoretic decentralized and centralized traffic signal controllers. Dong et al [20] focused on multi-intersection.…”
Section: Gt-based Signal Control Studiesmentioning
confidence: 99%
“…Additionally, they also extended their work to the network level [18]. Furthermore, Elouni et al [19] compared the operation of game theoretic decentralized and centralized traffic signal controllers. Dong et al [20] focused on multi-intersection.…”
Section: Gt-based Signal Control Studiesmentioning
confidence: 99%
“…Using two methods-game-theoretic decentralized and centralized perimeter control-Elouni et al [68] designed an adaptive traffic signal control system and compared the performance of both methods. Findings indicated that the Nash Bargaining (NB) traffic signal controller can prevent congestion from building and improve the entire network's performance.…”
Section: Signalized Roadway Applicationsmentioning
confidence: 99%
“…The NB controller outperforms both gating and non-gating controllers with significant reductions in vehicle travel time, emissions, fuel consumption, and delays. Specifically, the decentralized NB controller led to significant reductions of, with or without gating, 21% to 41% in total delay, 40% to 55% in CO2 emission levels, and 12% to 20% fuel consumption [54].…”
Section: Signalized Roadway Applicationsmentioning
confidence: 99%